Pleural fluid glucose testing using a finger stick glucometer: a novel bedside test - Abdo, Tony F. (J Thorac Dis, 2019)
BACKGROUND: Pleural fluid glucose (PFG) has diagnostic and therapeutic implications for the management of pleural effusion. The literature examining point-of-care testing of PFG is limited, and no studies exist for the bedside measurement of PFG using a glucometer (B-PFG). In this study, we compared the accuracy of B-PFG measurement to standard in-lab measurement (Lab-PFG). METHODS: Patients undergoing thoracentesis or thoracostomy were enrolled. PFG was measured at the bedside with a finger stick blood glucometer (ACCU-CHEK(®) Inform II, Roche) and in the laboratory. Two consecutive measurements were taken using the glucometer, and their mean was compared to the glucose concentration measured in the laboratory. Pearson correlation coefficient and Bland-Altman Plot analysis were used to compare the two measurements. RESULTS: Sixty patients were included. Mean age was 64.1 years. Forty-nine patients had exudative effusions (41% malignant, 26% parapneumonic, and 33% others). There was a significant correlation between the B-PFG and the Lab-PFG (r=0.98, 95% CI of 0.97 to 0.99; P<0.0001). There was good agreement between the B-PFG and the Lab-PFG with a mean difference of 14.8 mg/dL [95% limit of agreement (LOA) of −2.2 to 31.8 mg/dL]. This agreement was even better at glucose values less than 80 mg/dL. CONCLUSIONS: PFG measured at the bedside with a glucometer closely correlates with the laboratory measurement. Further studies are needed prior to incorporating this test in clinical practice.